In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be x + 3 = 48 => x = 45 or (x + 1) = 48 => x = 47 However, at least one of these solutions fails to work when substituted back into the original equation. Why is that? Please help Eric to understand better; solve the problem yourself, and explain your reasoning. Will someone please help me

Discussion problems suck.

i know... i hate em... its my final exam and im trying to get through been doing it all day

we have to use the FOIL method to multiply them on the left side of the equation. (x + 3)(x + 1) = 48 \[x^2+4x+3=48 \]\[x^2+4x−45\] When we are going to solve it further by factorization, we will solve it like: \[x^2 + 4x -45 = 0\]\[x^2 + 9x -5x -45 = 0 \] Taking commons: x(x+9) -5(x+9) =0 Therefore: (x+9)(x-5) So solutions are: x = -9 & x = 5

I was about to do it, got the same answer :)

LOL.

Did taht worked @87??

what?

yes... i got one more will u help me?

Sure, post it on left. ^.^ Dont forget to hit good answer.

Join our real-time social learning platform and learn together with your friends!